2018
DOI: 10.1016/j.virusres.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and transmission of alphasatellite, betasatellite and tomato yellow leaf curl virus in susceptible and Ty-1 -resistant tomato plants

Abstract: Begomoviruses (family Geminiviridae) are frequently associated with alphasatellites and betasatellites in the Old World. Tomato yellow leaf curl virus, one of the most damaging begomovirus species worldwide, was recently found associated with betasatellites in the eastern coast of the Mediterranean Sea, and in the Middle East region. Tomato yellow leaf curl virus (TYLCV)/betasatellite associations were shown to increase TYLCV virulence in experimental conditions. The sustainability of TYLCV/satellite associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Recently, Conflon et al () reported on the compromising effect of a co‐replicating betasatellite on Ty‐1 resistance. Ty‐1 tomato lines co‐infected with different TYLCV strains and a cotton leaf curl Gezira betasatellite revealed an increase in disease symptoms, but interestingly titres only increased in the mixed infection case with TYLCV‐Il, while those of TYLCV‐Mld were decreased on addition of the betasatellite.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Conflon et al () reported on the compromising effect of a co‐replicating betasatellite on Ty‐1 resistance. Ty‐1 tomato lines co‐infected with different TYLCV strains and a cotton leaf curl Gezira betasatellite revealed an increase in disease symptoms, but interestingly titres only increased in the mixed infection case with TYLCV‐Il, while those of TYLCV‐Mld were decreased on addition of the betasatellite.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of honeysuckle yellow vein mosaic betasatellite (HYVMVB), TYLCVinfected tomato plants developed more severe stunting symptoms [55]. A recent study showed that co-replication of TYLCV-IL with CLCuGB leads to a significant increase of TYLCV symptoms (Figure 4) [58]. In the Mediterranean basin and the Middle East, which are proposed to be centers of both TYLCV complex origin and diversification, the first betasatellite (i.e., CLCuGB) associated with either TYLCV-IL or TYLCV-Mld in tomato plants was identified very recently in Israel [12,21,59].…”
Section: Alarming Scenario: Role Of Betasatellites In Tylcv Epidemicsmentioning
confidence: 99%
“…TYLCV has been spread around the world due to the spread of the vector whitefly, the international trade in tomato seedlings and possibly even tomato fruit 4,63,64 . The fear that a disease enhancing, TYLCV-adapted betasatellite such as ToLCB could spread with the virus, has been noted previously 18,65 . The results here raise the additional possibility that other viruses, including viruses not adapted to plants of the Solanaceae such as MYMIV, could be moved around the world as a passenger to TYLCV in tomato.…”
Section: Discussionmentioning
confidence: 96%